Fluktuasi Aktivitas Enzim SGOT dan SGPT pada Pasien Kanker Payudara yang Menjalani Kemoterapi di RSUD Provinsi NTB - Fadila Rizki Ananda; Erlin Yustin Tatontos; Fihiruddin Fihiruddin (Poltekkes Kemenkes Semarang, 2025)
Chemotherapy is one of the primary treatment for breast cancer. Despite its effectiveness, chemotherapy has the potential to cause hepatotoxicity due to drug metabolism in the liver. This condition is generally indicated by elevated levels of SGOT and SGPT enzymes. Liver enzyme monitoring is essential to assess hepatocellular function throughout the course of therapy. This research aims to determine fluctuations in SGOT and SGPT enzyme activity in breast cancer patient undergoing chemotherapy at the NTB Provincial Hospital, and describe the pattern of changes in enzyme values based on the frequency of chemotherapy cycles. An analytical observational study with a cross-sectional approach was employed. Samples were selected purposively based on the medical records of breast cancer patients who underwent 1 to 6 cycles of chemotherapy between January and December 2024. Data were analyzed descriptively based on the distribution and the average of SGOT and SGPT enzyme levels. The results showed fluctuating SGOT and SGPT levels across different chemotherapy cycles. There was no consistent pattern of increase in enzyme activity based on chemotherapy frequency. The average SGOT levels from cycle 1 to 6 were 24, 28, 27, 30, 33, and 24 IU/L, while the average SGPT levels were 35, 27, 29, 25, 29, and 29 IU/L, with a range of SGOT values of 13-404 IU/L and SGPT with a range of 5-304 IU/L. most enzyme values remained within normal range. It was concluded that chemotherapy frequency did not show a consistent association with increased SGOT and SGPT activity. These research emphasize the importance of routine monitoring of liver function during each chemotherapy cycle, so that potential hepatotoxicity can be adjusted according to the patient condition.